Freeze–thaw condition limits the fermentation process and accelerates the aerobic deterioration of oat (Avena sativa) silage in the Qinghai-Tibet Plateau - Li, Haiping; Guan, Hao; Jia, Zhifeng; Liu, Wenhui; Ma, Xiang; Liu, Yong; Wang, Hui; Zhou, Qingping (Frontiers in Microbiology, 2022)
The objective of this study is to determine the effect of freeze-thaw condition on the fermentation characteristics, microbial community and aerobic stability of oat (Avena sativa) silage in the Qinghai-Tibet Plateau. Oat forage was harvested at milk ripening stage, ensiled in vacuum-sealed bags, and then stored at (1) a constant temperature of 20℃, as a control (20 group) or (2) subjected to freeze-thaw condition (alternating 20℃ and -5℃ every 12 h; S group). The quality and microbial community in the silage were measured after 1, 3, 7, 14, and 60 days of ensiling, and the aerobic stability was measured after 60 days of ensiling at room temperature or at the two treatment temperatures. The results showed that the higher the pH, the lower the concentration of lactic acid and the ratio of lactic acid/acetic acid of the samples under freeze-thaw condition, as compared to those stored at 20℃. The dry matter content of the two treatment groups was significant difference (P<0.05); the content in the 20 group was higher than that in the S group. By contrast, the contents of ash, Neutral detergent fiber (NDF), Acid detergent fiber (ADF), Crude protein (CP), and Water-soluble carbohydrates (WSC) in the two groups were not significant different (P<0.05). The most prevalent bacterial genera included Lactobacillus spp., Leuconostoc spp., and Weissella spp. in all treatment conditions. The abundance of Lactobacillus spp. in the 20 group was highest on day 3 of ensiling, and that of lactic acid bacteria Lactobacillus spp. in the S group reached its peak on day 14, the abundance in all silage samples did not exceed 50% of the whole fermentation process, and the lactic acid concentration was significant correlated with Leuconostoc spp. The abundance of Enterobacterales in the S group was high. The aerobic stability of the S group was lower than that of the 20 group. Taken together, the freeze-thaw condition led to insufficient fermentation degree of silage by limiting the fermentation of microorganisms and severely reduced the aerobic stability of oat silage.